WAWASAN HADIS TENTANG ALAT DAN MEDIA PENDIDIKAN - Zainal Abidin (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Hadith is Everything that is based on the Prophet Muhammad PBUH from words, deeds, taqrir or nature. Educational tools are everything that serves to support the achievement of educational goals or anything that helps the implementation of education in achieving educational goals, both tools in the form of objects and non-objects. Whereas the media of education or learning is an object that can be sensed, especially vision and hearing, both inside and outside the classroom, which is used as a liaison tool (communication media) in the process of interaction in teaching and learning to improve the effectiveness of student learning outcomes. In the history of his life, the Prophet Muhammad PBUH being the Messenger of Allah also had a role as an educator who delivered and taught the message of the great Islamic religion. In the process of teaching the Messenger of Allah. has used tools and media in the form of objects or non-objects that helped him in educating students who at that time were early Muslims who in science terms Hadith known as the Companions of the Prophet. Recorded in the master books of the Prophet's Hadith, Muhammad PBUH have used several educational tools and media in the process of teaching to Muslims at that time known as the generation of friends in the term of Hadith science. The tools and media that were used by the Prophet Muhammad. is the person of the Prophet Muhammad PBUH itself then some things like silk and gold, sun, moon, pulpit, fingers, pictures and photos.